An Imperfect Totality: Some Notes on Spacial Composites and Film Propaganda - Arlauskaitė, Natalija (Politologija, 2018)
[only abstract in English; full article and abstract in Lithuanian] The article asks how coherent a narrative ideology really is and how total is the control of narrative in film propaganda developed for the Baltic States in the immediate aftermath of WWII. In 1947, three films for the newly occupied Baltic countries were produced by Lenfilm and Mosfilm in cooperation with the local studios: Marytė (directed by Vera Stroyeva) for Lithuania, Life in a Citadel (Elu tsitadellis, directed by Herbert Rappaport) for Estonia and Homeward with Victory (Mājup ar uzvaru, directed by Aleksandr Ivanov) for Latvia. These films served as an introduction of the Soviet visual regime to the new territories and trained new citizens to learn its political optics. The narrative ideology of all three films aims both at creating a thematic consistency and establishing a continuity of time and space usual for this kind of cinema wherever it is produced. However, a certain kind of narrative rupture appears in each of them – here they are called spacial composites. Typically, spatial composites are a vehicle for the utopian thinking when used as a tool in films produced by the power and a point of subversion when produced by the counterculture. The article argues that narrative film propaganda survives this kind of rupture, harmless for the work of ideology. However, it marks a relative instability of hegemony while it’s in its initial stage.